Multi-omics analysis in human retina uncovers ultraconserved cis-regulatory elements at rare eye disease loci - Victor Lopez Soriano; Alfredo Dueñas Rey; Rajarshi Mukherjee; Genomics England Research Consortium; Frauke Coppieters; Miriam Bauwens; Andy Willaert; Elfride De Baere (Nature Communications, 2024)
Abstract Cross-species genome comparisons have revealed a substantial number of ultraconserved non-coding elements (UCNEs). Several of these elements have proved to be essential tissue- and cell type-specific cis-regulators of developmental gene expression. Here, we characterize a set of UCNEs as candidate CREs (cCREs) during retinal development and evaluate the contribution of their genomic variation to rare eye diseases, for which pathogenic non-coding variants are emerging. Integration of bulk and single-cell retinal multi-omics data reveals 594 genes under potential cis-regulatory control of UCNEs, of which 45 are implicated in rare eye disease. Mining of candidate cis-regulatory UCNEs in WGS data derived from the rare eye disease cohort of Genomics England reveals 178 ultrarare variants within 84 UCNEs associated with 29 disease genes. Overall, we provide a comprehensive annotation of ultraconserved non-coding regions acting as cCREs during retinal development which can be targets of non-coding variation underlying rare eye diseases.